2012
DOI: 10.1007/s13277-012-0356-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum HE4 as a diagnostic and prognostic marker for lung cancer

Abstract: We evaluated the diagnostic and prognostic efficacy of human epididymis protein 4 (HE4) for lung cancer patients by using our novel enzyme-linked immunosorbent assay (ELISA) system. We measured serum HE4 levels of cancer patients including 49 lung cancer and 18 ovarian cancer patients. Furthermore, we evaluated the relationship between serum HE4 levels and overall survival after chemotherapy of 24 lung cancer patients. Serum HE4 levels were significantly higher for non-small, small cell lung cancer and ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 22 publications
7
47
3
Order By: Relevance
“…HE4 expression has been demonstrated in several lung cancer cell lines [9,79]. The highest HE4 tissue expression was detected in adenocarcinomas of the lung compared with small-cell, squamous, and large-cell lung cancers [81,82]. Nagy et al reported that serum HE4 was highly increased in male patients with lung cancers, even prior to asymptotic cases, indicating serum HE4 could be a sensitive marker for early diagnosis of lung cancer [83].…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…HE4 expression has been demonstrated in several lung cancer cell lines [9,79]. The highest HE4 tissue expression was detected in adenocarcinomas of the lung compared with small-cell, squamous, and large-cell lung cancers [81,82]. Nagy et al reported that serum HE4 was highly increased in male patients with lung cancers, even prior to asymptotic cases, indicating serum HE4 could be a sensitive marker for early diagnosis of lung cancer [83].…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…HE4 has been reported to be upregulated in several types of cancers including those of the ovary (16), endometrium (17), lung (18,19), breast (7,15), stomach and pancreas (20). The expression of HE4 in ovarian cancer was initially reported in 1999 (16), and it was subsequently cleared as a new biological marker of ovarian cancer in 2003 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Iwahori et al (17) found elevated levels of serum HE4 not only in SCLC patients (88.9%, 8/9 patients) but also in NSCLC patients (90.0%, 36/40 patients). One significant study examined SCC and AC patients separately and found that HE4 serum levels were 125.05±89.06 and 357.04±220.40 pmol/l, respectively (18).…”
Section: Discussionmentioning
confidence: 97%